IS COLLEGE THE ONLY WAY! - Gilman, Stephen (The Accounting Review, 1937)
Abstract Under various sponsorships, certain proposals are being made which may bring about a complete reorganization in public accounting practice. These proposals may be sound. They may lead to a public accounting renaissance. They may, in fact accomplish a thing that all accountants have for years eagerly sought-higher standards in public accounting. But certainly these proposals should be analyzed and they should be subjected to acid test of intelligent and far-seeing consideration. It would be most unfair to ascribe all of this sponsorship to self-interest. Motives of these various groups are mixed. It is quite natural for university teachers to have complete faith in their own work. It cannot be said that the sponsorship of this movement by professors and instructors in accounting is wholly due to self-interest. The sponsorship of this movement by an organized group of non-certified public accountants represents a seeming contradiction. Without going into technical exposition, bills for all practical purposes will open doors.